Quality of Life in Patients with an Implantable Cardioverter Defibrillator: A Systematic Review - Tomzik, Juliane; Koltermann, Katharina C.; Zabel, Markus; Willich, Stefan N.; Reinhold, Thomas (Frontiers in Cardiovascular Medicine, 2015)
Despite the indisputable mortality advantages of implantable cardioverter defibrillators (ICDs), no consensus exists regarding their impact on quality of life (QoL). This systematic review investigates differences in QoL between patients with ICDs and controls. We systematically searched the MEDLINE, EMBASE, Cochrane, Web of Science, and PsychINFO databases. Articles were included if they were published after the year 2000 and reported on original studies with a control group. Five randomized controlled trials with a total of 5,138 patients and 10 observational studies with a total of 1,513 patients met the inclusion criteria. Nine studies found comparable QoL for ICD recipients and patients in the control groups, three studies found an increased QoL for ICD patients, and three studies found a decreased QoL for ICD patients. The question of whether QoL relates to ICD therapy cannot be answered conclusively due to the heterogeneity of the existing studies. Lower QoL was apparent among patients with an ICD who experienced several device discharges. Medical staff should be particularly aware of the signs of both psychological and physical disorders in these patients. Further investigations on QoL in ICD patients are desirable, but ethical reasons restrict the conduct of randomized trials.